Indonesia is Combating Corruption: A Struggle between the Extra-Ordinary Measurement and Extraordinary People - Dini Dewi Heniarti (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2016)
Currently, the practices of the mafia of law in Indonesia is getting more rampant. Law enforcement is very slow, many cases of corruption offenses as crimes extra ordinary crime are addressed will slow grind lower law. The ineffective of law in Indonesia is also dependent on these factors. Primarily extraordinary people. Several law enforcement officials are easily bribed by corrupt actors with the aim to escape punishment or lighten their sentences. Laws are formulated to deal with the corruption that seems barren. Factually  Indonesia shows that is still ranked below Malaysia, Singapore, and Hong Kong, as well as Vietnam and the Philippines. The outcome in the form of impacts and benefits of combating corruption unclear to this day. This paper will to describe that law enforcement combating corruption will be supported by extraordinary measures and extraordinary people. Especially, Indonesia, a majority Muslim country in fact the largest Muslim country in the world, a large number of Islam is really potential become a leader in combating corruption.